SISTEM INFORMASI GEOGRAFIS PADA APLIKASI DESA PINTAR BERBASIS MOBILE - Gresa Pranata Simarmata; Fati Gratianus Nafiri Larosa; Jimmy Febrynus Naibaho (Universitas Methodist Indonesia, 2020)
The villages in the Andam Dewi sub-district, Central Tapanuli have not maximally utilized information from the Central Bureau of Statistics (BPS). The information obtained using Google Maps is still standard and does not represent the potential of the villages in the sub-district. One of the efforts to further encourage the economy is to encourage the development of villages based on local wisdom, natural resources, and their uniqueness so that they can become innovative and creative villages. The Geographical Information System in the Mobile-Based Smart Village Application was created to make it easier for the government, community, tourists, and potential investors to find information on village potentials such as fisheries, plantations, trade, tourism, culture, and public services. This system is built using the PHP and Java programming languages and MySQL as the database. The result of this research is a mobile-based geographic mapping application.